INTEGRASI NILAI PENDIDIKAN ISLAM MULTIKULTURAL PADA LEMBAGA BAHASA ASING DI PONDOK PESANTREN NURUL JADID PAITON - Agus Sulthoni Imami (Institute Agama Islam Al-Qolam Malang, 2022)
The integration of multicultural Islamic educational values ​​in foreign language institutions is discussed within the framework of critical discourse analysis from the aspects of the textual dimension, discourse analysis, and social practice. The role of foreign language institutions is seen as linguistic ideological constitutional institutions that have a dialectical relationship with the local culture of the language's origin, so that it is suspected that they are not in accordance with the function of Islamic boarding schools. Based on the background above, the researcher wants to analyze the integration of multicultural Islamic educational values ​​in foreign language institutions at the Nurul Jadid Paiton Islamic Boarding School, Probolinggo. The focus of this research is (1) exploring the model, process, and strategy of integrating the values ​​of Multicultural Islamic Education in foreign language institutions, and (2) Interpreting the contribution of the results of integrating the values ​​of Multicultural Islamic Education in foreign language institutions. This research uses a qualitative approach with a case study type. Data collection was carried out by observation, interviews, and documentation, research subjects were determined based on purposive sampling, data analysis techniques were carried out by condensing data, presenting data, verifying, and drawing conclusions. The results of the study show that the integration of multicultural Islamic education in the foreign language institution at Pondok Pesantren Nurul Jadid is carried out well through curriculum, extracurricular activities, Santri organizations and collaboration between institutions. This integration process shows good results and does not interfere with the main focus of Pondok Pesantren as a religious institution.